Back-contacted hybrid organic–inorganic perovskite solar cells. Issue 15 (29th March 2016) - Jumabekov, A. N.; Della Gaspera, E.; Xu, Z.-Q.; Chesman, A. S. R.; van Embden, J.; Bonke, S. A.; Bao, Q.; Vak, D.; Bach, U.
Abstract : A novel architecture for quasi-interdigitated electrodes (QIDEs) allows for the fabrication of back-contacted perovskite solar cells. Abstract : A novel architecture for quasi-interdigitated electrodes (QIDEs) allows for the fabrication of back-contacted perovskite solar cells. The devices showed a stable power output of 3.2%. The design of the QIDEs avoids the defects that cause short-circuiting in conventional IDEs, while enhancing the collection area of the electrodes. Photoluminescence and photocurrent mapping is used to probe the charge generation and transport properties of the perovskite solar cells.